Normative study of theme identifiability: Instructions with and without explanation of the false memory effect (2016)
False-memory illusions have been widely studied using the Deese/Roediger–McDermott paradigm (DRM). In this paradigm, words semantically related to a single nonpresented critical word are studied. In a later memory test, critical words are often falsely recalled and recognized. The present normative study was conducted to measure the theme identifiability of 60 associative word lists in Spanish that include six words (e.g., stove, coat, blanket, scarf, chill, and bonnet) that are simultaneously associated with three critical words (e.g., HEAT, COLD, and WINTER; Beato & Díez, Psicothema, 26, 457–463, 2011). Different levels of backward associative strength were used in the construction of the DRM lists. In addition, we used two types of instructions to obtain theme identifiability. In the without-explanation condition, traditional instructions were used, requesting participants to write the theme list. In the with-explanation condition, the false-memory effect and how the lists were built were explained, and an example of a DRM list and critical words was shown. Participants then had to discover the critical words. The results showed that all lists produced theme identifiability. Moreover, some lists had a higher theme identifiability rate (e.g., 61 % for the critical words LOVE, BOYFRIEND, COUPLE) than others (e.g., 24 % for CITY, PLACE, VILLAGE). After comparing the theme identifiabilities in the different conditions, the results indicated higher theme identifiability when the false-memory effect was explained than without such an explanation. Overall, these new normative data provide a useful tool for those experiments that, for example, aim to analyze the wide differences observed in false memory with DRM lists and the role of theme identifiability